EKSPLORASI ETNOMATEMATIKA KERAJINAN ANYAMAN "BELUNGKUR" PADA MASYARAKAT DUSUN PENJULUNG KECAMATAN TELUK KERAMAT KABUPATEN SAMBAS - Zea Zea; Hamdani Hamdani; Romal Ijuddin (Jurnal AlphaEuclidEdu, 2022)
The purpose of this study is to identify the mathematical concepts involved in the craft of weaving belungkur in the Penjulung Hamlet community in Teluk Keramat district, Sambas Regency. The research method used was a descriptive exploratory ethnographic method. The subjects of this study were 2 weaving belungkur artisans. The data in this study are the results of interviews, observations, and recordings. The results obtained from this study are that the numbers mentioned in regional languages include one meaning one, dua' meaning two, tige meaning three, ammpat meaning four, limma' meaning five, annam meaning six, tujoh meaning seven, lapan meaning eight, semilan meaning nine. and sepuloh meaning ten. The results of the study also found that the shape of the curved surface was in the form of a rectangle and at the edges of the bend there was also a triangular shape. Measurements using the limbs such as the length of the hand is dapa' and finger is kilan. All the results obtained can be integrated into learning math at school.